Review of Anthobaris Hustache and description of a new species from Costa Rica (Coleoptera, Curculionidae, Baridinae) - Prena, Jens (Zootaxa, 2022)
The small Neotropical weevil genus Anthobaris Hustache, 1951 is studied for the first time since its description. Anthobaris affabra of authors [=Baridius affaber Boheman, 1844] is distinguished from the true A. affabra [=Centrinus affaber Boheman, 1844] and removed from the genus. Three species are recognized: the type species A. rugosicollis Hustache, 1951 from Argentina and Bolivia, A. affabra (Boheman, 1844) new combination from Brazil, and A. comptior Prena new species from Costa Rica. Anthobaris denticulata Hustache, 1951 is a junior subjective synonym of A. affabra (new synonymy). Collections of A. rugosicollis from Santa Cruz Department, Bolivia suggest that these weevils might be associated with the sunflower genus Smallanthus (Compositae).